2018
DOI: 10.18203/2320-1770.ijrcog20183797
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices about cervical cancer screening among nursing staff in rural tertiary care center

Abstract: Background: Cervical cancer is the second most common cancer among women worldwide.  The knowledge and attitude of nursing personnel towards cervical cancer screening can grossly influence the community. As the doctor to patient ratio is low in India, staff nurses if trained can act both as health educators and service providers. Objectives of the study were to determine the baseline information about the knowledge of cervical cancer and explore attitude and practice of Pap smear screening among staff nurses.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
3
11
1
Order By: Relevance
“…Cervical cancer screening through Pap smear could be very effective in detecting cervical neoplasia at a primordial stage, and this could be precipitated by a very effective treatment. Only 30% of the respondents knew that screening should begin at 21 years, which is comparable to 46% and 54.1% of respondents that knew in studies by Vishwakarma et al, [12] and Shah et al, [14], respectively. Majority of the respondents in this study knew that HPV vaccination was a preventive measure against cervical cancer, and this is a similar finding to a study that reported that 82.7% of the participants pointed HPV as a preventive measure, [16].…”
Section: Discussionmentioning
confidence: 62%
“…Cervical cancer screening through Pap smear could be very effective in detecting cervical neoplasia at a primordial stage, and this could be precipitated by a very effective treatment. Only 30% of the respondents knew that screening should begin at 21 years, which is comparable to 46% and 54.1% of respondents that knew in studies by Vishwakarma et al, [12] and Shah et al, [14], respectively. Majority of the respondents in this study knew that HPV vaccination was a preventive measure against cervical cancer, and this is a similar finding to a study that reported that 82.7% of the participants pointed HPV as a preventive measure, [16].…”
Section: Discussionmentioning
confidence: 62%
“…Among 22 studies reviewed, 19 studies 15 25 , 27 – 30 , 32 35 reported knowledge of cervical cancer. The overall knowledge of cervical cancer among health professionals was 75.14%.…”
Section: Resultsmentioning
confidence: 99%
“…The awareness level of risk factors was adequate. Among 22 studies, 14 studies 14 , 15 , 17 – 21 , 24 , 25 , 28 , 29 , 33 35 reported knowledge of risk factors of cervical cancer. The most common risk factor known was multiple sexual partners 44.07%, HPV infection 40.85%, and early age of marriage 38.52% ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of other studies indicate that women do not know at what specific age they have to conduct cervical cancer screening. If they do not know at what age they need to begin the screening, all women are at risk of cervical cancer [10].…”
Section: Introductionmentioning
confidence: 99%